The Effect of Educational Interventions Through Animated Video and Booklet on Parents’ Knowledge Regarding Cognitive Stimulation in Preschool-Aged Children - Divya Adelia; Ferika Indarwati; Rahmah Rahmah; Istinengtyas Tirta Suminar (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Cognitive stimulation supports preschool children's learning and development, yet parents may need accessible guidance for providing age appropriate stimulation at home. Objective: To evaluate whether education using an animated video combined with a booklet was associated with greater short-term improvement in parents' knowledge of cognitive stimulation than leaflet education. Methods: A quasi experimental pretest posttest control group study included 120 parents recruited purposively from different early childhood education institutions (60 intervention; 60 control). The intervention group received a 2-minute animated video plus booklet for one week, whereas the control group received a leaflet. Knowledge was scored from 0 to 25. Results: Mean knowledge increased from 11.72±3.17 to 18.03±3.31 in the intervention group and from 11.27±3.93 to 13.52±3.37 in the control group. The between group difference in mean change was 4.06 points (95% CI, 3.25-4.87; p<0.001; Cohen d=1.14). Conclusion: The multimedia intervention was associated with a larger short-term knowledge gain than leaflet education, although nonrandom site allocation limits causal interpretation.